THEORETICAL FUNDAMENTALS ON REPRESENTATION OF THE PICTURE OF THE WORLD THROUGH TEXTUAL MOTIVATION - Н. М. Савчук (Записки з українського мовознавства, 2017)
In the article the theoretical fundamentals of representation of fictional picture of the world through the prism of textual motivation have been outlined; the relationship between the concepts of motivation, motivisation as key notion in the sphere of word formation, theory of nomination and cognitive onomasiology has been set; the definition of fictional text has been given: it is a special functional system, in which the word formation meanings as others are influenced by artistic conventions, that contributes to the transformation of meanings, imaginative rethinking of common language meanings; the theoretical principles of textual motivation (position of the author) and its decryption (position of the reader) as a cognitive process in the representation of fictional picture of the world have been formulated: textual motivation is a factor of decryption of author’s meanings, revealing the depth of which depends on the interpretation of incentive structures and codes.